Kajian Penentuan Lokasi Tempat Pemrosesan Akhir Sampah Kabupaten Serang Menggunakan Analisis Sistem Informasi Geografis - Frebhika Sri Puji Pangesti; Ma’ruf Hidayat; Ade Ariesmayana (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Serang Regency has a problem in waste management because it does not have a final processing site since 2009. The Cilowong landfill, which originally belonged to Serang Regency, was transferred to Serang City in 2009. It is necessary to conduct research that aims to determine the location of the Waste Final Processing Site in Serang Regency. This research uses a quantitative descriptive method with spatial analysis using Geographic information systems. Determination of the location of waste landfills uses SNI 03-3241-1994 concerning procedures for selecting the location of final landfills. The study results show that Serang Regency has 11 locations suitable for landfill, and also shows that Serang Regency has 2 recommended locations for landfill. Location 1 is located in the Sindangmandi village area, Baros sub-district with a land area of 71.83 Ha. Location 2 is in the Tanjungsari village area of Pabuaran Subdistrict with a land area of 79.06 Ha.